Van der Waals Epitaxy of Horizontally Orientated Bismuth Iodide/Silicon Heterostructure for Nonvolatile Resistive‐Switching Memory with Multistate Data Storage. Issue 17 (12th July 2020) - Li, Chia‐Shuo; Kuo, Sheng‐Wen; Wu, Yu‐Tien; Chang, Po‐Hang; Ni, I‐Chih; Chen, Mei‐Hsin; Wu, Chih‐I
Abstract: The film quality of insulators significantly affects performance of resistive random‐access memories (RRAMs), particularly in current leakage and degradation. In this study, a facile and practical method is employed to achieve the van der Waals epitaxy of bismuth iodide (BiI3 ) on silicon by using a self‐assembled monolayer of octadecyltrichlorosilane (OTS) as a buffer layer. The BiI3 layer is compact and has high crystallinity, a pinhole‐free, and compact surface; every BiI3 crystal is horizontally aligned with OTS–Si substrate. The RRAMs with the Si ++ /OTS/BiI3 /Au structure exhibit excellent resistive switching properties with a very high on/off ratio of 10 9, long‐term stability for data retention, high endurance in write–erase cycles, and multistate information storage capacity. The crystal orientation, anisotropic carrier transport, morphology, deposition rate, and roughness considerably influence the resistive switching results. These are thoroughly investigated by analyzing the current–voltage characteristics at various temperatures, scanning electron microscope, atomic force microscope, X‐ray photoemission spectroscopy, and X‐ray diffraction patterns. It is proposed that the resistive switching mechanisms is caused by the iodine ion migration, which changes the valence charge of bismuth. This leaves a partially formed conductive metallic bismuth filament in the BiI3 layer under the electrical field that enables multistate data storage. Abstract : Van der Waals epitaxy of bismuth iodide (BiI3 ) is achieved by using a self‐assembled monolayer of octadecyltrichlorosilane (OTS) as a buffer layer on silicon. Resistive switching devices with the Si ++ /OTS/BiI3 /Au structure exhibit excellent resistive switching properties with a very high on/off ratio of 10 9, long‐term stability for data retention, high endurance in write–erase cycles, and multistate information storage capacity.